Factors contributing to COVID-19 skepticism and information gaps among older adults in the United States and Canada: An analysis of nationality, gender, education, family, and politics - Lund, Brady D.; Long, Bobbi Sartin (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2022)
This study examines relationships between demographic attributes of older adults, information challenges surrounding the COVID-19 pandemic, and skepticism about the efficacy of COVID-19 preventative measures (social distancing, mask wearing, good hygiene). A 12-question survey was distributed on the Amazon Mechanical Turk platform in late June 2021, receiving 400 responses. Findings indicate that gender, political affiliation, relationship status, family closeness, and perceived family control over one’s information source preferences are the greatest predictors of elevated gaps in information and skepticism towards COVID-19 prevention. Specifically, in this study, married, conservative men with close family ties often expressed elevated inadequacy of information and COVID-19 skepticism.